Evaluación de 32 poblaciones f2 de arroz (oryza sativa l.) provenientes de cruces simples. - Ortiz Avila, Engels Jamil (2013)
This study was related evaluating 32 F2 populations of rice (Oryza sativa L.) single crosses from two witnesses and infomercials are the variety lNlAP – 14 and promising line GO-39691 was conducted at the Estación Experimental Litoral Sur “Dr. Enrique Ampuero Pareja", located at Km 26 via Duran Tambo, Yaguachi, Virgen of Fatima. Is located at 17 m, 2 ° 15 'south latitude and 79 º 54' west longitude, with annual temperature of 26 º C, average annual rainfall of 1025 mm, and 83% of annual average relative humidity. The objectives of this research were to determine the phenotypic characteristics in 32 F2 segregating populations of rice through individual selection of plants and identify the best production segregating F2 and select high-quality F2 lines long and crystalline grains.